2008
DOI: 10.1128/aem.01951-07
|View full text |Cite
|
Sign up to set email alerts
|

Depth-Resolved Quantification of Anaerobic Toluene Degraders and Aquifer Microbial Community Patterns in Distinct Redox Zones of a Tar Oil Contaminant Plume

Abstract: Microbial degradation is the only sustainable component of natural attenuation in contaminated groundwater environments, yet its controls, especially in anaerobic aquifers, are still poorly understood. Hence, putative spatial correlations between specific populations of key microbial players and the occurrence of respective degradation processes remain to be unraveled. We therefore characterized microbial community distribution across a high-resolution depth profile of a tar oil-impacted aquifer where benzene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
216
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(228 citation statements)
references
References 57 publications
12
216
0
Order By: Relevance
“…The method is simple, rapid, has a high resolution and good repeatability, and produces quantitative results; with these advantages it has been widely used to study the diversity of a variety of microbial communities [11][12][13]. Since the application of molecular biological techniques overcomes the limitations of traditional methods based on culture, it provides a more accurate estimate of the richness and evenness on the level of genes and identifies variation in species, which provides a more objective insight in the community composition of fungi present in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…The method is simple, rapid, has a high resolution and good repeatability, and produces quantitative results; with these advantages it has been widely used to study the diversity of a variety of microbial communities [11][12][13]. Since the application of molecular biological techniques overcomes the limitations of traditional methods based on culture, it provides a more accurate estimate of the richness and evenness on the level of genes and identifies variation in species, which provides a more objective insight in the community composition of fungi present in the environment.…”
Section: Introductionmentioning
confidence: 99%
“…From a total of 87 bacterial 16S rRNA gene clones, 3 were identified as chimeric and excluded from further analysis. Phylogenetic trees were reconstructed from sequence data as described (Winderl et al, 2007(Winderl et al, , 2008. All sequences generated in this study have been deposited with GenBank and can be found under the accession numbers GU133208-GU133309.…”
Section: Nucleic Acid Extraction and Ultracentrifugationmentioning
confidence: 99%
“…Cloning, sequencing and phylogenetic analysis Amplicons generated with the primer sets Ba27f (Weisburg et al, 1991)/907r (Muyzer et al, 1995) (same as for T-RFLP) and 7772f/8546r (Winderl et al, 2007) were cloned and sequenced (Winderl et al, 2007(Winderl et al, , 2008) from selected gradient fractions (one 'light' and one 'heavy' 16S rRNA gene library, as well as one bssA gene library from a the same 'heavy' fraction). Selected terminal restriction fragments (T-RFs) predicted in silico for representative clones were verified in vitro (see Table 1).…”
Section: Nucleic Acid Extraction and Ultracentrifugationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the upstream, 12 clones comprising two OTUs associated with heavy metal resistance from polluted sediment had high similarity with Thiobacillus sp., each OTU was respectively isolated from Hg polluted sediment and leachate sediment (Regier et al, 2012;Liu et al, 2011). In the downstream, one OTU of a total of 18 clones were highly similar to Hydrogenophilaceae from the anaerobic environment in tar oil contaminant plume (Winderl et al, 2008).…”
Section: Comparison Of Taxonomic Composition Of Upstream and Downstrementioning
confidence: 99%